Disturbed microbiota-metabolites-immune interaction network is associated with olfactory dysfunction in patients with chronic rhinosinusitis - Han, Xingyu; He, Xuejia; Zhan, Xiaojun; Yao, Linyin; Sun, Zhifu; Gao, Xing; Wang, Shan; Wang, Zhenlin (Frontiers in Immunology, 2023)
Purpose: Olfactory dysfunction (OD) is a debilitating symptom frequently reported by patients with chronic rhinosinusitis (CRS) and it is associated with a dysregulated sinonasal inflammation. However, little information is available about the effect of the inflammation-related nasal microbiota and related metabolites on the olfactory function in these patients. Therefore, the current study aimed to investigate the nasal microbiota-metabolites-immune interactions and their role in the pathogenesis of OD in CRS patients. Methods: 23 and 19 CRS patients with and without OD, respectively, were enrolled in the present study. The “Sniffin’ Sticks” was used to measure the olfactory function, while the metagenomic shotgun sequencing and the untargeted metabolite profiling were performed to assess the differences in terms of the nasal microbiome and metabolome between the two groups. The levels of nasal mucus inflammatory mediators were investigated by a multiplex flow Cytometric Bead Array (CBA). Results: A decreased diversity in the nasal microbiome from the OD group compared to the NOD group was evidenced. The metagenomic analysis revealed a significant enrichment of Acinetobacter johnsonii in the OD group, while Mycoplasma arginini, Aeromonas dhakensis, and Salmonella enterica were significantly less represented (LDA value > 3, p < 0.05). The nasal metabolome profiles were significantly different between the OD and NOD groups (P < 0.05). The purine metabolism was the most significantly enriched metabolic subpathway in OD patients compared with NOD patients (P < 0.001). The expressions of IL-5, IL-8, MIP-1α, MCP-1, and TNF were statistically and significantly increased in the OD group (P < 0.05). All these data, including the dysregulation of the nasal microbiota, differential metabolites, and elevated inflammatory mediators in OD patients demonstrated a clear interaction relationship. Conclusions: The disturbed nasal microbiota-metabolite-immune interaction networks may be implicated in the pathogenesis of OD in CRS patients and the underlying pathophysiological mechanisms need to be further investigated in future studies.